Diversidade de inimigos naturais e redes de interações com vespas e abelhas solitárias - Silva, Guilherme Gonzaga da (2019)
Natural enemies are one of the main regulating agents of populations. Among the natural enemies, those who adopt parasitism as strategy dominate the food webs. The hosts, on the other hand, have anti-parasitism strategies to escape the selective pressure that these natural enemies exert. Behavioral variation consists of a repertoire of individual choices that allow the body to respond quickly to the action of natural enemies. However, anthropogenic impacts have altered and even extinguished behavioral responses in many organisms. Habitat anthropization and landscape fragmentation consist of some of the major anthropogenic nowadays. Solitary wasps and bees have been used as models for biology and ecology studies because of easiness of collection with the trap-nests methodology. These hymenoptera also have potential as bioindicators of ecosystem status. Moreover, presenting great behavioral variety during nesting activity. However, few studies address the interactions of wasps and solitary bees with natural enemies and the factors that influence parasitism. Thus, the present study aimed to analyze the diversity of natural enemies and their networks of interactions with solitary hymenoptera that occur in a fragmented landscape composed of Cerrado fragments in restoration process, Eucalyptus plantation and riparian forest. In addition, we sought to identify which individual behavioral variations affect host parasitism rates. The areas presented similar diversity, with a significant difference only between Eucalyptus and riparian forest, which presented fewer species of natural enemies. The networks obtained were not nested and showed a greater tendency to generalist species in the silviculture area in relation to other predominant physiognomies in the study areas. The areas of Cerrado and riparian forest presented a higher index of specialization and modularity. The analyzes of factors influencing parasitism showed a nesting site effect, nest diameter and mean cell size only for Trypoxylon lactitarse. There was no correlation to Centris analis and Tetrapedia diversipes species. We conclude that human impact on landscapes may alter the diversity of natural enemies and limit their interactions with hosts. It is also concluded that differences in the biology of taxa make it difficult to identify the factors that affect parasitism in solitary bees.